Optimal fertigation start time and frequency in cabbage seedlings - Silva Neto, Onésio Francisco da; Moreira, Édimo Fernando Alves; Torres, José Luiz Rodrigues; Castoldi, Renata; Luz, José Magno Queiroz; Hamilton César de Oliveira, Hamilton César de Oliveira (Comunicata Scientiae, 2022)
Although cabbage is one of the most important vegetables in Brazil, seedling production is carried out empirically by producers, given that there are no literature reports on the optimal start time and management strategy for seedling fertigation. The present study aimed to assess the influence of fertigation management on the development of cabbage seedlings, in order to determine the best start time and application intervals for nutrient supply. The study consisted of two experiments conducted in a randomized block design, with six repetitions each. The first involved six fertigation start times (0, 3, 6, 9, 12 and 15 days after emergence) and the second consisted of five treatments, that is, five fertigation application frequencies (every 3, 4, 5, 6 and 7 days after the first application). Biometric, physiological and nutrient characteristics were assessed when the seedlings reached the ideal (commercial) transplanting stage. Fertigation start times had a significant effect on the number of leaves, shoot and root dry weight, leaf area and macronutrient accumulation. The best results were obtained for a start time of 0 to 6 days after emergence (DAE). Application intervals had a significant effect only on calcium and sulfur accumulation. It was concluded that cabbage seedling fertigation should start three days after emergence, adopting a four-day application interval.